2002
DOI: 10.1590/s0103-50532002000500028
|View full text |Cite
|
Sign up to set email alerts
|

Trichloroisocyanuric Acid: An Alternate Green Route for the Transformation of Alkenes into Epoxides

Abstract: Epóxidos podem ser preparados eficientemente a partir da reação de alquenos com ácido tricloroisocianúrico em acetona aquosa seguido de tratamento da cloroidrina resultante com KOH aquoso em éter / pentano.The preparation of epoxides is efficiently achieved in mild conditions by reaction of alkenes with trichloroisocyanuric acid in aqueous acetone followed by treatment of the resulting chlorohydrin with aqueous KOH in ether / pentane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 12 publications
0
14
0
4
Order By: Relevance
“…and Bentonit Brasgel TM (0.2 g) clay in aqueous dioxane at room temperature. After 4 hours, KOH was added in a biphasic system 13 (hexane/water) to produce the pure epoxides in excellent yields after 30 min. The HRGC of these crude reactions indicated the respective epoxide as the unique product.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…and Bentonit Brasgel TM (0.2 g) clay in aqueous dioxane at room temperature. After 4 hours, KOH was added in a biphasic system 13 (hexane/water) to produce the pure epoxides in excellent yields after 30 min. The HRGC of these crude reactions indicated the respective epoxide as the unique product.…”
Section: Resultsmentioning
confidence: 99%
“…12 Although this methodology is effective, the handling and manipulation of toxic and corrosive halogens is problematic (especially in large-scale), then the search for alternative sources of electrophilic halogen is of great interest. 13 Recently, we have developed a green and consistent route to iodohydrins by coiodination of alkenes with water (reaction of alkenes with I 2 / H 2 O) catalyzed by some clayminerals. 14 Our results showed that natural Brazilian clays F-117 (a smectite) and F-101 (an interstratified structure with smectite, kaolinite and mica as clay-minerals) proved to be superior to commercial KSF™ and K-10™ clays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The products were characterized by spectroscopic methods and, wherever possible, by coinjection in HRGC with authentic commercial samples or prepared by an alternative route. 13 In summary, NCSac and NBSac are alternative and attractive reagents to perform halogenation of electron rich aromatic compounds and cohalogenation of alkenes. Furthermore, the reaction conditions are simple, safe and these halosaccharins are easily prepared by commercial sodium saccharin.…”
Section: Resultsmentioning
confidence: 99%
“…7 This compound is extensively used as a disinfectant agent for swimming pools (algicide and bactericide). 8 Presently, TCI is also widely employed as an effective chlorinating reagent for various chemical reactions, such as the α-chlorination of carbonyl derivatives, 9 the production of nitriles from amines, 10 the halogenation and epoxidation of alkenes, 11 and the chlorination of aromatic systems, 5,12 among others; extensive reviews on the reactions of TCI have been offered by Tilstan and Weinmann, 4 Cunha and Ferreira 13 and Mendonça and Mattos. 14 Figure 1 shows the chemical structures of these molecules.…”
Section: Introductionmentioning
confidence: 99%